A calculus problem by Muhammad Shariq

Calculus Level pending

If f ( x ) = ln ( n = 0 x n + 1 ( n ) ! ) \large f(x)=\ln\left(\displaystyle \sum_{n=0}^\infty \frac{x^{n+1}}{(n)!}\right) then f ( 1 ) = a b \large f'(1)=\frac{a}{b} where a \large a and b \large b are co-prime positive integers. Compute a + b \large a+b .


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Muhammad Shariq
Dec 31, 2013

We first look at the Taylor Series and observe that:

n = 0 x n + 1 n ! = x + x 2 + x 3 2 ! + . . . + x n + 1 n ! = x ( 1 + x + x 2 2 ! + . . . + x n n ! ) = x e x \large \displaystyle \sum_{n=0}^\infty \frac{x^{n+1}}{n!}=x+x^2+\frac{x^3}{2!}+...+\frac{x^{n+1}}{n!}=x(1+x+\frac{x^2}{2!}+...+\frac{x^n}{n!})=xe^x

Then:

f ( x ) = ln ( x e x ) = ln ( x ) + ln ( e x ) = ln ( x ) + x f ( x ) = 1 x + 1 f ( 1 ) = 2 1 \large f(x)=\ln(xe^x)=\ln(x)+\ln(e^x)=\ln(x)+x \implies f'(x)=\frac{1}{x}+1 \implies f'(1)=\frac{2}{1}

Therefore a + b = 2 + 1 = 3 \large a+b=2+1=\boxed{3} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...